Myocardial global longitudinal strain: An early indicator of cardiac interstitial fibrosis modified by spironolactone, in a unique hypertensive rat model - Leader, Catherine J.; Moharram, Mohammed; Coffey, Sean; Sammut, Ivan A.; Wilkins, Gerard W.; Walker, Robert J. (PloS one, 2019)
Is global longitudinal strain (GLS) a more accurate non-invasive measure of histological myocardial fibrosis than left ventricular ejection fraction (LVEF) in a hypertensive rodent model. Hypertension results in left ventricular hypertrophy and cardiac dysfunction. Speckle-tracking echocardiography has emerged as a robust technique to evaluate cardiac function in humans compared with standard echocardiography. However, its use in animal studies is less clearly defined. Cyp1a1Ren2 transgenic rats were randomly assigned to three groups; normotensive, untreated hypertensive or hypertensive with daily administration of spironolactone (human equivalent dose of 50 mg/day). Cardiac function and interstitial fibrosis development were monitored for three months. The lower limit of normal LVEF was calculated to be 75%. After three months hypertensive animals (196±21 mmHg systolic blood pressure (SBP)) showed increased cardiac fibrosis (8.8±3.2% compared with 2.4±0.7% % in normals), reduced LVEF (from 81±2% to 67±7%) and impaired myocardial GLS (from -17±2% to -11±2) (all p<0.001). Myocardial GLS demonstrated a stronger correlation with cardiac interstitial fibrosis (r2 = 0.58, p<0.0001) than LVEF (r2 = 0.37, p<0.006). Spironolactone significantly blunted SBP elevation (184±15, p<0.01), slowed the progression of cardiac fibrosis (4.9±1.4%, p<0.001), reduced the decline in LVEF (72±4%, p<0.05) and the degree of impaired myocardial GLS (-13±1%, p<0.01) compared to hypertensive animals. This study has demonstrated that, myocardial GLS is a more accurate non-invasive measure of histological myocardial fibrosis compared to standard echocardiography, in an animal model of both treated and untreated hypertension. Spironolactone blunted the progression of cardiac fibrosis and deterioration of myocardial GLS.